O morar na praia: transformações e permanências na moradia litorânea em Caucaia – CE - Paz, Francileuda Pontes (2020)
As it is an open space to the diverse socio-spatial dynamics, the metropolitan tourist space is shown as a set of transformations resulting from the actions of the social agents that produce the coastal urban space and the dynamics caused by tourism and by vilegiature. The contextualization of these transformations becomes pertinent from the coastal housing destined to the low income classes, in order to contextualize the practice of living in gentrified and segregated coastal spaces. Thus, the aim is to understand how low-income classes live on the beach in coastal areas with investments concentrated in tourism and leisure in the municipality of Caucaia - Ceará durig the transition from the 20th to the 21st century. The methodological procedures of the research were developed and based on the Regressive-Progressive method of Henri Lefebvre (1949). Operationally, classes of up to 2 minimum wages of total household income were listed as the main group to be analyzed in relation to urban housing in Cumbuco and Tabuba cities. Therefore, the numerical and georeferenced database of the Instituto Brasileiro de Geografia e Estatística (IBGE) and the Instituto de Pesquisa e Estratégia Econômica do Ceará (IPECE) was used to characterize the study area and its surroundings. Additionally, semi-structured interviews were carried out in order to identify the transformations and strategies for the permanence of the low-income class on the coast of Caucaia. As a result, an overview of the coast and the municipality of Caucaia was constructed; the formation of living spaces for income classes of up to 2 minimum wages was discussed; the occupation of environmentally fragile areas by social groups with lower incomes was verified, as measured by the process of enhancing the coastal strip of Cumbuco and Tabuba; the change in the way of life and in the work activities of residents installed in the spatial area under analysis in this research was identified.